Gerenciamento e Acesso a Documentos na Internet através de XML, RDF e Ontologia - Chaves, Marcirio (2012)
The World Wide Web was built to be used by people, however, it must be also legible to machines. Most of the documents nowadays available in the Web is identified only by layout information. Facing the need of providing better automatic access to the amount of information available in the Web, it is necessary to use the XML (eXtensible Markup Language) technology, which allows the semantic exploration of the contents of these documents. This work presents a study on the techniques for organization, presentation and search of information through the Web. The XML technology has been used to mark the data from case study document – UNISINOS’ subject characterization, willing to identify semantically its parts. In order to associate and represent information about teachers and subjects on the Internet, RDF (Resource Description Framework), an application XML, was used, allowing adding formal semantics to the Web. The definition of the main concepts, relations and restrictions represented on the RDF is formally described in an ontology for domain university. The ontology and the RDF easy the framework and the access to documents in the Web, as by machines, as by people, allowing a better identification of the meaning of its content in a domain. Based on XML technology, on application RDF and on the ontology, which form the “Semantic Web” term, we try to add semantics to available data on the Internet in order to improve information search and exhibition.